Progesterone Treatment Shows Benefit in Female Rats in a Pediatric Model of Controlled Cortical Impact Injury - Geddes, Rastafa I.; Peterson, Bethany L.; Stein, Donald G.; Sayeed, Iqbal (PloS one, 2016)
We recently showed that progesterone treatment can reduce lesion size and behavioral deficits after moderate-to-severe bilateral injury to the medial prefrontal cortex in immature male rats. Whether there are important sex differences in response to injury and progesterone treatment in very young subjects has not been given sufficient attention. Here we investigated progesterone's effects in the same model of brain injury but with pre-pubescent females. Twenty-eight-day-old female Sprague-Dawley rats received sham (n = 14) or controlled cortical impact (CCI) (n = 21) injury, were given progesterone (8 mg/kg body weight) or vehicle injections on post-injury days (PID) 1-7, and underwent behavioral testing from PID 9-27. Brains were evaluated for lesion size at PID 28. Lesion size in vehicle-treated female rats with CCI injury was smaller than that previously reported for similarly treated age-matched male rats. Treatment with progesterone reduced the effect of CCI on extent of damage and behavioral deficits. Pre-pubescent female rats with midline CCI injury to the frontal cortex have reduced morphological and functional deficits following progesterone treatment. While gender differences in susceptibility to this injury were observed, progesterone treatment produced beneficial effects in young rats of both sexes following CCI.